A History of Christian Faith Church International (CFCI), in Ghana - Eduah, F.O. (University of Ghana, 2018)
Christian Faith Church International (CFCI) is a Pentecostal Church founded by an illiterate indigenous Ghanaian charismatic figure over three decades ago in Takoradi, in the Western Region of Ghana. The church since it broke away from a classical Pentecostal church, that is, Christ Apostolic Church (CAC), in the Western Region of Ghana in 1983 had experienced relatively some significant growth in membership and in expansion particularly in the Western Religion of Ghana. For some time now in the history of Ghanaian Pentecostalism, many scholars have written about classical and neo Pentecostal churches in Ghana yet not much is written about Pentecostal churches from that part of the country. This research work set out to study a history and doctrines; explore the reasons for the growth and governance of the Christian Faith Church International (CFCI) and investigate the churches contributions to Ghanaian and worldwide African Indigenous churches/ Pentecostal movements, since it was established. The problem of this study is that the activities and impacts of growth of the church that has been comparatively slow and lower than its contemporaries at the time of its establishment. This is the reason why the main objective of this work seek to interrogate the factors that might have contributed to its pace of growth. To achieve the set objectives, the research adopted the historical and the sociological approaches in data collection and analysis. Also, the researcher used both primary and secondary sources in the data collection. The data collected and analysis revealed that the growth of the church in the Western Region of Ghana where the church was first established, seems to be the largest in terms of membership and expansion, however, the growth is rather limited to just the South-Eastern part of the Region The church is virtually not existing in the South-Western and the Northern part of the Region. Also, vernacular (Fanti language) as a policy to be used by all its branches, in its liturgy had been a factor of growth in that part of Ghana. The church seems to be doing everything possible to fulfil its vision and mission which is to bring the unsaved to the saving knowledge of Christ. The relevance of this study is to be able to add to academia the activities and impacts of the church from that Region of Ghana to Christian missions. It is also, to bring to the awareness of the leadership of the church the negative or positive factors that are contributing to the growth rate of the church. Finally, the researcher recommend that the policy of missions/evangelism had to be redefined by the church and be given much more priority or focus than it is currently receiving. Also, they should establish a well-trained missionary group or movement that is well resources, and tasked with the responsibility on missions than what exist currently.
MPhil.
Keywords: Christian Faith Church International (CFCI); Ghana